2018
DOI: 10.3389/fcimb.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

Route of Glucose Uptake in the Group a Streptococcus Impacts SLS-Mediated Hemolysis and Survival in Human Blood

Abstract: The transport and metabolism of glucose has been shown to have far reaching consequences in the transcriptional profile of many bacteria. As glucose is most often the preferred carbon source for bacteria, its presence in the environment leads to the repression of many alternate carbohydrate pathways, a condition known as carbon catabolite repression (CCR). Additionally, the expression of many virulence factors is also dependent on the presence of glucose. Despite its importance, little is known about the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The release of cytokines in db/db mice increased 4–8 h after injection ( Figures 3E – H ), indicating that cytokine production was followed by an increase in glucose concentrations. Sundar et al (2018) found that the hemolytic activity of GAS correlates with the glucose concentration. However, it is unknown how blood glucose and insulin concentrations are associated with the pathogenicity of SDSE in animal models of DM.…”
Section: Discussionmentioning
confidence: 99%
“…The release of cytokines in db/db mice increased 4–8 h after injection ( Figures 3E – H ), indicating that cytokine production was followed by an increase in glucose concentrations. Sundar et al (2018) found that the hemolytic activity of GAS correlates with the glucose concentration. However, it is unknown how blood glucose and insulin concentrations are associated with the pathogenicity of SDSE in animal models of DM.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the observed glucose-induced Mga phosphorylation phenotypes could be that glucose may have a lesser effect on modulating PTS than other undefined sugar sources. Glucose can enter the cell independently of the PTS ( Fiegler et al., 1999 ) and Sundar and colleagues showed that glucose transport in S. pyogenes is primarily through the non-PTS GlcU transporter and converted to glucose-6-phosphate by the NagC glucose kinase ( Sundar et al., 2018 ). Nevertheless, results from Hondorp et al., 2013 and Valdes et al., 2018 suggest that Mga activity is a direct consequence of glucose availability, which in turn alters the availability of phosphates that can be transferred from PTS proteins to Mga ( Hondorp et al., 2013 ; Valdes et al., 2018 ).…”
Section: Catabolic Signals That Regulate Pcvrsmentioning
confidence: 99%
“…In Vibrio cholerae , PTS modulates virulence gene expression by regulating the expression of tcpH and aphAB to control the expression of toxT , the central activator of virulence gene expression (Wang et al 2015 ). A promiscuous man-family PTS transporter of Streptococcus exerted influence on SLS-mediated hemolysis and the route of glucose uptake impacting their survivals in human blood (Sundar et al 2017 ; 2018 ). In a mouse model, the impairments in PTS components in Bacillus anthracis and Borrelia burgdorferi attenuated in vivo virulence via affecting the expression of their master virulence regulators, respectively (Khajanchi et al 2016 ; Bier et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%